Oil Spill and Socioeconomic Vulnerability in Marine Protected Areas - Silva, Felipe Roberto da; Schiavetti, Alexandre; Malhado, Ana Cláudia Mendes; Ferreira, Beatrice; Sousa, Caio Victor de Paula; Vieira, Fábio Pessoa; Pinto, Francisco Roberto; Souza, Gabriel Barros Gonçalves de; Olavo, George; Santos, Jéssica Borba Quintela dos; Campos-Silva, Joao Vitor; Oliveira Júnior, José Gilmar Cavalcante de; et al. (Frontiers in Marine Science, 2022)
The extensive oil spill (> 2,900 km) that occurred in the southwestern Atlantic (2019/2020) increased the vulnerability of the Brazilian coast, affecting marine and coastal protected areas (MPAs). In addition to supporting conservation, MPAs are sustainably used by local populations to help maintain ocean-dependent livelihoods. In this sense, we aim to assess the socioeconomic vulnerability of human communities in MPAs affected by this major oil spill. Using digital mapping, we assessed the socioeconomic vulnerability of 68 human communities living in or near 60 MPAs of different categories that were impacted by this spill. This is the first assessment of the vulnerability status of human populations under significant levels of poverty and social inequality, which are particularly dependent on healthy and effective Brazilian MPAs. More than 6,500 enterprises and institutions were mapped, including trade activities, services, tourism, and leisure venues. Most enterprises (34.4%) were involved in the food sector, related to the ocean economy, and, therefore, highly vulnerable to oil spills. Furthermore, the majority (79.3%) of the vulnerable activities are concentrated in multiple-use MPAs, with extractive reserves coming second and accounting for 18%. This result shows the high vulnerability of this tropical coast to oil accidents and the risks to food security for traditional communities. We also found a heterogeneous vulnerability indicator along the coast, with the most vulnerable regions having an undiversified economic matrix heavily dependent on activities such as fishing, family farming, tourism, accommodation, and the food sector. Thus, this study provides a tool to help prevent and mitigate economic losses and increases the understanding of the weaknesses of MPAs in the face of large-scale disasters, thus helping to build socioeconomic and ecological resilience.